HAZARD MANAGEMENT OF MULTI-STORY BUILDINGS’ NON-STRUCTURAL ELEMENTS IN THE FACE OF EARTHQUAKE: A LITERATURE REVIEW - Akhmadi Puguh Raharjo (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
Non-structural elements of multi-story buildings need to be taken into account in the mitigation of earthquake in order to ensure the safety of the occupants. The purpose of this study is to obtain information related to the hazard management of multi-story buildings’ non-structural elements from the authorities, namely FEMA and SPRINT-Lab. This study is a qualitative study focused on reviewing the information that is relevant for future adaptation in Indonesia. The collected literature was then analyzed descriptively. The results of this review underlined the three most important stages that became the focus of hazard management from multi-story buildings’ non-structural elements, namely: the process of identification, the process of prioritization and the process of determining mitigation actions that need to be taken. Future research should be focused on developing a methodology that can be used to calculate the risk level of building occupants by considering the number of occupants and the level of danger of each object present with the occupant's mobility pattern in a certain area and time.